Mathematical Induction

Solution: Given, n =3. 2n – 1 = (2 x 3) – 1 = 6 -1 = 5. So, LHS = 1 + 3 + 5 = 9. RHS = 3 2 = 9. Since, L.H.S = R.H.S. Hence, 1 + 3 +.+(2n-1) = n 2 for n = 3.

Problems on Principle of Mathematical Induction

Don’t worry; we’ve prepared more examples for you! Example 1 Show that the sum of the first n natural numbers can be determined using the formula, n ( n + 1) 2. Solution Our goal is to show

  • 461

    Teachers

  • 4.9/5

    Ratings

What clients say

  • Deal with math equations

    I can help you with any mathematic task you need help with.

  • Clear up math equation

    If you're struggling to clear up a math equation, try breaking it down into smaller, more manageable pieces. By taking a step-by-step approach, you can more easily see what's going on and how to solve the problem.

  • Save time

    One way to save time is to automate your tasks.